Time-dependent convergence response of drawpoint pillars during undercutting and early caving at the Oyu Tolgoi Panel 0 block cave - Batkhuu, B; Enkhtaivan, E; Biziyabal, A; Batbayar, B; Tsogtbaatar, L (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
Extraction level instability is one of the main challenges in block cave mining, particularly in deep, high-column caves where drawpoint service life is extended until the ore column is fully exhausted. Oyu Tolgoi Panel 0 (OTP0) is one of the deepest block caving operations globally and is characterised by severe squeezing‑type drawpoint failure resulting from highly faulted rock masses subjected to high in‑situ stress and substantial column loading. This study investigates the time‑dependent evolution of drawpoint damage at OTP0 using multiple deformation and convergence monitoring techniques. Continuous monitoring data are analysed to identify the progressive development of rock mass deformation and the primary mechanisms controlling drawpoint instability over time. The results reveal distinct deformation stages associated with key phases of the caving process, including undercutting, drawbell establishment, and cave propagation. These stages are governed by a combination of mining-induced stress redistribution, time-dependent rock mass behaviour, and geological controls such as faults and weak zones. The findings provide improved insight into the deformation mechanisms of highly deformable rock masses in block caving environments and support more informed strategies for undercut design, drawpoint management, and ground support planning in deep, high-stress caving operations.
Keywords: block caving; convergence monitoring; time-dependent deformation; pillar damage